2009
DOI: 10.1182/blood-2008-07-168468
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 blockade with ipilimumab to treat relapse of malignancy after allogeneic hematopoietic cell transplantation

Abstract: Relapse of malignancy after allogeneic hematopoietic cell transplantation (allo-HCT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
224
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(243 citation statements)
references
References 22 publications
3
224
1
2
Order By: Relevance
“…A single dose of ipilimumab in patients who relapsed after allogeneic SCT appeared to be safe with no case of severe GvHD reported among 29 patients. 30 A French study of nivolumab in r/r cHL after allogeneic SCT reported limited toxicity and no cases of significant GvHD, 35 which is in contrast to preliminary results of an ongoing trial of ipilimumab in relapsed malignancies after allogeneic SCT reported at ASH 2015. 83 This trial included 28 patients, five of whom had drugrelated toxicities leading to treatment discontinuation, including three cases of grade 3 chronic liver GvHD and one case of acute intestinal GvHD.…”
Section: Toxicity Of Immune Checkpoint Inhibitioncontrasting
confidence: 48%
See 3 more Smart Citations
“…A single dose of ipilimumab in patients who relapsed after allogeneic SCT appeared to be safe with no case of severe GvHD reported among 29 patients. 30 A French study of nivolumab in r/r cHL after allogeneic SCT reported limited toxicity and no cases of significant GvHD, 35 which is in contrast to preliminary results of an ongoing trial of ipilimumab in relapsed malignancies after allogeneic SCT reported at ASH 2015. 83 This trial included 28 patients, five of whom had drugrelated toxicities leading to treatment discontinuation, including three cases of grade 3 chronic liver GvHD and one case of acute intestinal GvHD.…”
Section: Toxicity Of Immune Checkpoint Inhibitioncontrasting
confidence: 48%
“…30 On the other hand, preliminary results of an ongoing phase II trial of pembrolizumab in r/r CLL patients, including those with Richter syndrome, showed an ORR of 21% in 20 evaluable patients. Responses, including one CR, were documented in three patients with Richter syndrome and also in patients in whom prior ibrutinib therapy had failed.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In Phase II studies less than 1 in 100 treated patients developed Grade 3 or 4 cough, dyspnea or pleural effusion [15]. There is only one previous report of autoimmune pulmonary toxicity related to ipilimumab administration [16]. The adverse pulmonary events, dyspnea and pneumonitis, occurred in patients treated with ipilimumab who had relapsed haematologic malignancies after allogeneic haematopoetic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%